Why Does Fixation Persist? Experimental Evidence on the Judgment Performance Effects of Expensing Intangibles - Luft, Joan L.; Shields, Michael D. (The Accounting Review, 2001)
This study shows experimentally that when individuals use information on intangibles expenditures to predict future profits, expensing (vs. capitalizing) the expenditures significantly reduces the accuracy, consistency, consensus, and self-insight of individuals' subjective profit predictions. The experimental design allows us to eliminate several competing explanations for this apparent fixation on accounting. Subjects do not base their judgments on a nai¨ve prior belief that expensing precludes effects on future profits; a preexperiment question shows that subjects expect intangibles expenditures will affect future profits even when expensed. Moreover, subjects do not lack, or fail to use, data that would allow them to learn the exact expenditure-profit relation. They receive data on intangibles expenditures and profits as a basis for learning, and in some respects the learning is quite successful even when intangibles are expensed; subjects' profit predictions accurately reflect the mean and standard deviation of actual profits. Nevertheless, consistent with psychological theories of learning, subjects do not learn the exact magnitude of the effect of intangibles on future profits as well when the intangibles are expensed. Although the mean of their predictions is accurate, they do not discriminate well between cases with high and low actual profits. In consequence, their prediction accuracy, consistency, consensus, and self-insight are lower when intangibles are expensed. Thus, in this case, learning does not mitigate fixation on accounting, because accounting affects the learning process itself.